Identity, Ethnicity and School Experiences: Relocated Montserratian Students in British Schools - Shotte, Gertrude (Refuge: Canada’s Journal on Refugees, 2006)
This paper explores the issues of identity and ethnicity that confront relocated Montserratian students in British schools. It begins with a brief historical review of the ongoing volcanic crisis, then explains the circumstances within which the issues are framed. The paper argues that the merging of “old” and “new” forms of identity and ethnicity has affected relocated students’ aspirations in various ways. Montserrat’s education system evolved out of a colonial British-based curriculum that encouraged particular morals, which are not apparent in the British school system. These values remain an integral part of the Montserrat mores and thus are recognized as central to the island identity. In adjusting to their new cultural environment, relocated students have donned new identities that have inevitably clashed with traditional norms. This paper therefore explains how they have negotiated their ethnic/racial identities in relation to school and home, and how they have crafted new identities, while at the same time trying to maintain a desired level of “Montserratness.” The assessment and inferences made in this paper are based on formal and informal research conducted with relocated Montserratians, particularly students and their parents/guardians, in different regions, but the main location is London.